The Decade Show : Frameworks of Identity in the 1980s. - The New Museum of Contemporary Art, New York; The Studio Museum in Harlem (New York : Museum of Contemporary Hispanic Art, 1990)
Aguilera-Hellweg, Max ; Ahearn, John ; Alfonzo, Carlos ; Amos, Emma ; Applebroog, Ida ; Arai, Tomie ; Azaceta, Luis Cruz ; Basquiat, Jean-Michel ; Beerman, Miriam ; Bernal, Louis ; Birnbaum, Dara ; Brito-Avellana, Maria ; Brown, Fred ; Buchanan, Beverly ; Carvalho, Josely ; etc.
The Decade Show : Frameworks of Identity in the 1980s, Museum of Contemporary Hispanic Art, New York, May 16 to August 19, 1990 ; The New Museum of Contemporary Art, New York, May 12 to August 19, 1990 ; The Studio Museum in Harlem, May 18 to August 19, 1990
boek